(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
In this work, we investigate a time-delayed model describing the dynamics of the hematopoietic stem cell population with treatment. First we establish the existence of the steady states, trivial solution describing the extinction of the population and he nontrivial solution describing the persistence of the disease. Next, we analyze the asymptotic behavior of the model, and study the local asymptotic stability of steady states according to the delays values